DIRECT WET SEEDING AS AN ALTERNATIVE TO TRANSPLANTED RICE (ORYZA SATIVA) CULTIVATION IN ANDAMAN & NICOBAR ISLANDS - B. GANGAIAH; S. SWAIN; . SUBRAMANI (The Bioscan, 2019)
Field experiment was conducted in split plot design with five replications during 2015 kharif season at ICAR- CIARI, Port Blair, Andaman & Nicobar Islands, India. Main plot consisted of two establishment methods i.e. direct wet seeded rice (DWSR) and Transplanted rice (TPR) and sub plot consisted of four rice cultivars (Swarna, BPT-5204, CARI Dhan-6 varieties and US-312, a hybrid). The results revealed that DWSR crop maturing 12.2 days earlier with 52.9% higher panicle density (367.5/m2) but 24.8% lesser grains/panicle (103.8) has produced 0.47 and 2.08 t/ha higher grain and biological yield than TPR (3.81 and 8.68 t/ ha). The reduced cost of production (Rs. 10, 203/ha) on account of lower man power use (20 man days) together with higher yields in DWSR have resulted in 2.76 times more net income than TPR (Rs. 11,068/ha). Energy, fertilizer, rain water and per day productivity of DWSR were perceptibly higher than TPR. Among cultivars, Swarna (4.52 t/ha) on an average has 0.72 t/ha and 15,094 Rs/ha higher grain yield and net income than other three cultivars. Interaction effects indicate that DWSR is best for varieties and hybrid has similar performance under both establishment methods. The study establishes DWSR as economically promising to TPR.